Application of phototherapy in the treatment of psoriasis vulgaris - Sadowska, Magdalena; Lesiak, Aleksandra; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2019)
Psoriasis is a chronic inflammatory skin disease with a complex aetiology. One of the methods of treating psoriasis is phototherapy, and the main phototherapeutic modalities include NB-UVB and PUVA. Phototherapy is considered the first treatment choice in moderate to severe forms of the disease. In mild psoriasis, an indication to start phototherapy is unsatisfactory outcome of topical treatment. NB-UVB is the first choice of therapy, and PUVA is considered in cases where NB-UVB fails to provide a sufficient therapeutic effect. The benefits of phototherapy include high efficacy and a good safety profile. However, phototherapy requires compliance with appropriate rules of photoprotection, careful patient monitoring and assessment of eligibility for treatment. The study below presents the most recent data on the application of phototherapy in patients with psoriasis, including the principles of irradiation treatment in children and pregnant, women, as well as adverse effects and methods to prevent them.